2021
DOI: 10.3390/molecules26113151
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Ageing Potential of S. euboea Heldr. Phenolics

Abstract: In recent years, the use of Sideritis species as bioactive agents is increasing exponentially. The present study aimed to investigate the chemical constituents, as well as the anti-ageing potential of the cultivated Sideritis euboea Heldr. The chemical fingerprinting of the ethyl acetate residue of this plant was studied using 1D and 2D-NMR spectra. Isomeric compounds belonging to acylated flavone derivatives and phenylethanoid glycosides were detected in the early stage of the experimental process through 2D-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 60 publications
2
7
0
Order By: Relevance
“…4 c ). This is in accordance with previous findings in the specific plants 10 , 28 , 29 , 30 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 .…”
Section: Resultssupporting
confidence: 94%
See 1 more Smart Citation
“…4 c ). This is in accordance with previous findings in the specific plants 10 , 28 , 29 , 30 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 .…”
Section: Resultssupporting
confidence: 94%
“…4 c). This is in accordance with previous findings in the specific plants [10,[28][29][30][32][33][34][35][36][37][38][39][40].…”
Section: Resultssupporting
confidence: 94%
“…perfoliata with those of S. cypria, we compared them with NMR spectra of previously isolated compounds from our works in Sideritis spp. [5,8,9,12,13]. Through the screening of the 1 H-NMR spectra of different compounds, we carefully noticed that the main different hydrogen signals in the spectrum of infusion of S. perfoliata subsp.…”
Section: Resultsmentioning
confidence: 99%
“…The management of inflammation and neuropathic pain mainly succeed by the management of pro-inflammatory mediators (NF-κB, TNF-α, IL-1β, and IL-6) [ 12 , 13 ]. Other studies have demonstrated the anti-aging effect of Sideritis extracts, by anti-hyaluronidase activity [ 32 , 33 ] and the antimicrobial activities [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%